A Critical History of the Defining Features of Modern Science - Idowu, Oladele Daniel (NIU Journal of Social Sciences, 2020)
Modern Science has a long history of what differentiates it from other disciplines. Its separation from philosophy in the 16 th century marked its steady ascent into becoming the king of all knowledge-seeking disciplines. It is almost a given that science is a collection of facts; a body of knowledge that describes and explains the working of nature. The facts of science are fascinating and interesting, but they are not the very essence of science, rather, the excitement of science lies in its inquisitive and curious nature, its intriguing observations, its breath-taking experiments and mathematical proofs that defines its character and purpose. This paper attempts to dig out the defining features that distinguish modern science from other disciplines from its historical antecedents. It carries out a historical exegesis of the rise of modern science drawing out its defining characteristics, from the early Greek philosophers through the medieval era to modern times. It shows that the defining features of modern science are common place procedures carried out by people in their daily activities but, which, taken together as a research procedure, amount to one of the most powerful tools man has devised to know, to conquer, and to control nature.